PENGGUNAAN KAIDAH FIQHIYYAH âAL-KHURÅªJ MIN AL-KHILÄF MUSTAHABâ TERKAIT BAB IBADAH DALAM KITAB IâÄNAT AL THÄLIBÄªN - Munawaroh, Lathifah (NUANSA: Jurnal Penelitian Ilmu Sosial dan Keagamaan Islam, 2017)
This paper is trying to describe the rules of jurisprudence "Al-KhurÅ«j Min al-KhilÄfÂ  Mustahab " used by Sayyid Bakri in his book named IÄnat al ThÄlibÄ«n which is the explaination of book Fath al-MuÄ«n. This is quite important, especially in ethics in khilafiyah problems that occur in the chapters of jurisprudence as well as in order to carry prudence in religion. Precautions for cases that still in the difference of jurisprudence is ordered. In fact, it is said that including the shubhat cases are cases that occur differences in jurisprudence. Of course the rules of " Al-KhurÅ«j Min al-KhilÄfÂ  Mustahab " can not be applied absolutely unconditionally. However, in practice the scholars define a few terms, so that not all differences are mutabar and encouraged to get out of that difference.One of the unique that Sayyid Bakri did in this book, he used it in strengthening his opinion, and this paper only discusses how Sayyid Bakri use the rules of jurisprudence " Al-KhurÅ«j Min al-KhilÄf Mustahab ". This paper limits its application to the chapter Worship only: prayer , fasting, zakat and hajj.